Calcifying epithelial odontogenic tumor or compound odontoma: a case report in the left maxilla of a child with panoramic and CBCT imaging - Yusuf, Mohammad; Jawad, Ali; Tyas, Indah Widyaning (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: The aim of this case report is to describes the importance of advanced imaging such as CBCT 3D to make diagnosis rather than just a panoramic radiography. Case Report: A 12-year-old girl patient came for the third time with her parents to the radiology installation after being referred from the oral surgery clinic at RSIGM SA due to complaints of swelling on the right side of the face that had not healed. The patient was initially diagnosed as a calcifying epithelial odontogenic tumor This is based on hematological and histopathological examinations. At the second visit patient had marsupialization and panoramic examination performed. The panoramic results show that the lesion is still developing as seen from the change in the distance between the lesion to the surrounding tissue. The image of the radiopaque lesion is surrounded by radiolucency in the maxillary region from the apical of teeth 53 to 17, the lesion is multiple, unilateral, and irregular with ill-defined boundaries so that the appropriate radiodiagnosis is Calcifying Epithelial Odontogenic Tumor before doing CBCT 3D imaging on third visit. Conclusion: CBCT 3D was more accurate and reliable in diagnosing type of odontogenic tumor.